Public Image of Ganjar Pranowo on the News in @Oposisicerdas.com and @Tribunnews.com Twitter Accounts - Jingga, Jingga; Rustono, Rustono; Santoso, Bernadus Wahyudi Joko (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Critical discourse analysis (CDA) on Ganjar Pranowo’s pulic image is interesting to do because in CDA, discourse not understood as a language study but used to convey the ideology to influence readers. This research aims to find Ganjar Pranowo's public image in the news on @Oposisicerdas.com and Tribunnews.com Twitter accounts. This research uses the Norman Fairclough CDA method. The data source is discourse on @Oposisicerdas.com and @Tribunnews.com Twitter accounts from March to May 2023. The results of this study revealed Ganjar Pranowo's public image on @Oposisicerdas.com and Tribunnews.com Twitter accounts. Ganjar Pranowo's news construction on Twitter accounts @Oposisicerdas.com and @Tribunnews.com is in the form of interpretation of the discourse production process, discourse dissemination, and text consumption. Socio-cultural practices in Ganjar Pranowo's reporting on @Oposisicerdas.com and @Tribunnews.com are influenced by situational, institutional, and social aspects. This finding can cultivate sosial media news reader to be wiser in capturing information.